2010
DOI: 10.1007/s00221-010-2193-7
|View full text |Cite
|
Sign up to set email alerts
|

Altered digit force direction during pinch grip following stroke

Abstract: This study examined grip force development in individuals with hemiparesis following unilateral stroke. Eleven patients with chronic stroke with severe hand impairment and five age-matched neurologically intact subjects grasped an instrumented object between the index finger and thumb while fingertip forces, digit posture, and muscle electromyographic activity were recorded. We tested a range of different grip conditions with varying grip sizes, object stability, and grip force level. We found that fingertip f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 43 publications
3
72
0
Order By: Relevance
“…Valero-Cuevas provides a tool for measuring and quantifying anatomical structures which are crucial for grasp abilities of patients who have to undergo surgery (Valero-Cuevas and Laboratory 2000). Kamper is investigating human hands of healthy subjects and stroke patients for rehabilitation (Seo et al 2010). The ACT hand (Despande 2013) targets various issues, serving as a realistic model for surgeons to drypractice reconstructive surgery, but also to investigate neural control as well as for high-precision teleoperation and prosthetics.…”
Section: The Purpose Of the Modelsmentioning
confidence: 99%
“…Valero-Cuevas provides a tool for measuring and quantifying anatomical structures which are crucial for grasp abilities of patients who have to undergo surgery (Valero-Cuevas and Laboratory 2000). Kamper is investigating human hands of healthy subjects and stroke patients for rehabilitation (Seo et al 2010). The ACT hand (Despande 2013) targets various issues, serving as a realistic model for surgeons to drypractice reconstructive surgery, but also to investigate neural control as well as for high-precision teleoperation and prosthetics.…”
Section: The Purpose Of the Modelsmentioning
confidence: 99%
“…Rheumatoid arthritis, 8 osteoarthritis, 9 carpal tunnel disease 10 and stroke 11 have all been reported as having lower finger strengths. In addition to neurological disease causing lower strengths these can also cause deficits in control and direction of force application, 11 which are also required to co-ordinate functional tasks such as squeezing a bottle.…”
mentioning
confidence: 99%
“…Deficits in voluntary thumb extension (Lang et al 2009), grasp timing and production (Nowak and Hermsdorfer 2003;Raghavan et al 2006a), thumb grasp-force direction (Seo et al 2010), and thumb individuation (Raghavan et al 2006b) have been reported, but the exact causes of these impairments remain unclear. A number of studies have examined impairment mechanisms in the fingers (Cruz et al 2005;Kamper and Rymer 2001), but the issues for the thumb may differ.…”
mentioning
confidence: 99%